1991
DOI: 10.1007/bf02238497
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular fibrillation during transesophageal atrial pacing in an infant with Wolff-Parkinson-White syndrome

Abstract: A complication of transesophageal atrial pacing in an infant with Wolff-Parkinson-White syndrome (WPW) is reported. A newborn infant born with fetal hydrops had recurrent supraventricular tachycardia (SVT) that required repeated successful conversion by transesophageal atrial pacing. Because of secondary left ventricular dysfunction, digoxin was administered. During repeat transesophageal atrial pacing for recurrent SVT, ventricular fibrillation occurred. Although it is unclear which of several possible contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…1 VF has also been associated with a variety of therapeutic and diagnostic interventions, including the use of digoxin, 2-4 amiodarone, 5 and transesophageal pacing. 6,7 Spontaneous VF termination is rarely recognized, but has been recorded on ambulatory monitoring. 8,9 Two self-limited occurrences of apparent VF without antecedent AF or flutter in infants with WPW undergoing transesophageal electrophysiological studies are reported.…”
Section: Introductionmentioning
confidence: 99%
“…1 VF has also been associated with a variety of therapeutic and diagnostic interventions, including the use of digoxin, 2-4 amiodarone, 5 and transesophageal pacing. 6,7 Spontaneous VF termination is rarely recognized, but has been recorded on ambulatory monitoring. 8,9 Two self-limited occurrences of apparent VF without antecedent AF or flutter in infants with WPW undergoing transesophageal electrophysiological studies are reported.…”
Section: Introductionmentioning
confidence: 99%